2009
DOI: 10.2334/josnusd.51.425
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the external gonial angle in panoramic radiographs and lateral cephalograms of adult patients with Class I malocclusion

Abstract: The external gonial angle is an important angle of the craniofacial complex. It is significant for the diagnosis of craniofacial disorders. Lateral cephalogram and orthopantomograms can be used to determine this angle. In this study, we compared the external gonial angle determined from the two mentioned radiographs in Class I patients. We collected the radiographs of 70 patients with Angle's Class I (22 men and 48 women). The patients' age ranged from 15-30 years with a mean age of 18.24 years. The data gaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
3
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 8 publications
5
62
3
4
Order By: Relevance
“…Evidence shows that irrespective of whether GA measurements are obtained by lateral teleradiography or panoramic radiography, the results are compatible [23][24][25]. However, no records of GA measurements directly on the face of the individual, as in the method adopted by our study, were found.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Evidence shows that irrespective of whether GA measurements are obtained by lateral teleradiography or panoramic radiography, the results are compatible [23][24][25]. However, no records of GA measurements directly on the face of the individual, as in the method adopted by our study, were found.…”
Section: Discussioncontrasting
confidence: 46%
“…We did not find studies that performed GA evaluation directly on the face in the literature; however, in studies where the measurements were performed on radiographies, the values were 124.17 [24], 123 [23] and 127.07 [25] degrees. The comparison between GA values obtained by direct measurement or radiographies is not the purpose of this study; however, the proximity found is an important finding, since it gives credibility to the direct measurement on the face.…”
Section: Discussionmentioning
confidence: 82%
“…[5] The brightness and contrast enhancement and enlargement of the images provide an reproducible method of measuring the chosen points. [6,7] The measurements taken from mandibular ramus are subjected to linear discriminant function.…”
Section: Discussionmentioning
confidence: 99%
“…However, as compared with LCR, PR is not yet reliable enough to provide sufficiently accurate additional information (4). In addition, no reports have specified a detailed method for drawing the inferior border of the mandible (9,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Thus, the important points for tracing on film were reviewed in this report.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have evaluated the GA on PR, but no previous report described how to produce accurate, detailed images of the GA (9,11,(12)(13)(14)(15)(16)(17)(18)(19)(20). It is essential to develop a detailed method for drawing the inferior border of the mandible-in which only one line is made on the inferior border of the mandible-so as to not change the condition of the GA. Additionally, if the GA on PR is anatomically similar to the GA on LCR or has a characteristic structure, PR may prove to be more useful and could become a high-value-added dental examination.…”
Section: Introductionmentioning
confidence: 99%